34‐5: Invited Paper: C‐PS‐VA — Innovative LC Materials Enabling Super‐High Transmittance for High‐Resolution Displays. Issue 1 (28th June 2022) - Chuang, Susan; Chen, Fred; Chou, Ray; Hsieh, Joseph; Lin, Randy; Chen, Zoe
Abstract : In recent years, and for the next generation of TVs and monitors, increasing resolution is a key trend. One challenge is keeping the transmittance while pixel density increases. Chiral Polymer Stabilized Vertical Alignment (C‐PS‐VA) technology uses LC mixtures with higher birefringence and a chiral dopant and increases transmittance by more than 10% compared to conventional Polymer Stabilized Vertical Alignment (PS‐VA). This paper summarizes the recent developments of liquid crystal mixtures for C‐PS‐VA.